Adolescent suicide prevention programs: a systematic review (European Journal of Education and Psychology, 2024)
The aim of the study was to conduct a systematic review of suicide prevention programs in adolescents, guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. A search was conducted in international databases (PsycInfo, Scopus, and Web of Science), using inclusion criteria: (a) suicide prevention programs or mental health improvement; (b) targeting adolescents, or (c) adult training in adolescent suicide prevention. Studies from the last five years, from 2019 to 2023, were selected. Single case studies were excluded to avoid potential biases associated with individual studies. The initial sample consisted of 4,320 articles, while, after thorough analysis, the final sample comprised 20 articles with programs developed, primarily, in the United States (n = 7) and Australia (n = 5), mostly targeting adolescents aged 12-22 years (n = 18). Results supported the relevance of these programs in reducing suicidal ideation, increasing confidence, and familiarizing with suicide prevention tools and institutions. Activities focusing on detection, knowledge, and help-seeking were highlighted. In eight studies, it was found that the implemented program had a greater impact on females, as they put into practice the learnings from the workshops. In conclusion, the benefits of prevention against the risk of suicide in adolescents were confirmed, with some essential characteristics highlighted; furthermore, their limited presence in Spain offers an area of interest for work, indicating the importance of incorporating physical activity as a key aspect in addressing the pressure, depression, and stress associated with the risk of suicide in adolescents.
Keywords: program; prevention; suicide; adolescent